LITERATURE REVIEW THE INFLUENCE OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL SUPPORT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Hasyim, Wachid; Tukiran, Martinus (UJoST- Universal Journal of Science and Technology, 2024)
Organizational citizenship behavior (OCB) has become focus study management and behavior organizational. OCB defined as contribution volunteer individuals who exceed description their formal position. Study This aim conducta literature review about influence culture organization and support organizational towards OCB. Research methods is a literature review systematic with analyzed 10 articles study empirical 2014-2024. The results show that culture organization, satisfaction work, and commitment organization influential positive towards OCB. Supportive culture _ collaboration and attention to employees can increase OCB. Intelligence emotional and support Organizations also have an influence positive on OCB because fulfil need psychology and encourage reciprocity. In conclusion, culture positive and supportive organization organization in a way significant can increasing organizational citizenship behavior.